30-[15+7-(7- 3 -4)-2]- 3×7

asked by guest
on Jan 29, 2025 at 12:04 pm



You asked:

Evaluate the expression: 30(15+7(734)2)3730 - \left(15 + 7 - \left(7 - 3 - 4\right) - 2\right) - 3 \cdot 7

MathBot Answer:

30(15+7(734)2)37=1130 - \left(15 + 7 - \left(7 - 3 - 4\right) - 2\right) - 3 \cdot 7 = -11


30(15+7(734)2)37=30(15+7(44)2)37=30(15+702)37=30(15+7+02)37=30(22+02)37=30(222)37=302037=302021=1021=11\begin{aligned}30 - \left(15 + 7 - \left(7 - 3 - 4\right) - 2\right) - 3 \cdot 7& = 30 - \left(15 + 7 - \left(4 - 4\right) - 2\right) - 3 \cdot 7\\& = 30 - \left(15 + 7 - 0 - 2\right) - 3 \cdot 7\\& = 30 - \left(15 + 7 + 0 - 2\right) - 3 \cdot 7\\& = 30 - \left(22 + 0 - 2\right) - 3 \cdot 7\\& = 30 - \left(22 - 2\right) - 3 \cdot 7\\& = 30 - 20 - 3 \cdot 7\\& = 30 - 20 - 21\\& = 10 - 21\\& = -11\end{aligned}